L-Ascorbic Acid Shapes Bovine Pasteurella multocida Serogroup A Infection - Zhao, Guangfu; Li, Pan; Mu, Hao; Li, Nengzhang; Peng, Yuanyi (Frontiers in Veterinary Science, 2021)
Bovine Pasteurella multocida serogroup A (bovine PmA) is one of the most important pathogens causing fatal pneumonia in cattle. However, it is largely unknown how nutrition shapes bovine PmA infection. Here, we discovered the infected lung held the highest bacteria density than other tissues during infection. By screening the different metabolites between high (lung) and low (liver) bacteria density tissues, the present work revealed ascorbic acid and L-aspartic acid directly influenced bovine P. multocida growth. Interestingly, ascorbic acid, which expresses at higher level in the infected livers, inhibited bovine PmA growth as well as virulence factor expression and promoted macrophage bactericidal activity in vitro. In addition, ascorbic acid synthesize was repressed upon bovine PmA infection, and supplementation with exogenous ascorbic acid significantly reduced the bacteria burden of the infected lungs and the mice mortality. Collectively, our study has profiled the metabolites difference of the murine lung and liver during bovine PmA infection. And the screened ascorbic acid showed repression of bovine PmA growth and virulence expression in vitro and supplementation could significantly increase the survival rate of mice and reduce the bacterial load in vivo, which implied ascorbic acid could serve as a potential protective agent for bovine PmA infection in clinic.